If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3n + 7 = -4n Reorder the terms: 7 + -3n = -4n Solving 7 + -3n = -4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4n' to each side of the equation. 7 + -3n + 4n = -4n + 4n Combine like terms: -3n + 4n = 1n 7 + 1n = -4n + 4n Combine like terms: -4n + 4n = 0 7 + 1n = 0 Add '-7' to each side of the equation. 7 + -7 + 1n = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1n = 0 + -7 1n = 0 + -7 Combine like terms: 0 + -7 = -7 1n = -7 Divide each side by '1'. n = -7 Simplifying n = -7
| 8m-14=58 | | 5x+13=64 | | f(x)=x^6-3x^4+2x^4+8x^3-x^2-x+3 | | -2k+4k-4+5k= | | -7v+6=-6v | | 2+4x=8+x | | -12x+20=-x^2 | | 10-6j=-5j | | 3m^2-11m-20=0 | | 5x-10=4x+11 | | -52+10x=68 | | 4(4x+1)=3x-4(6-x)+3 | | 14p+q+4p+17q= | | -8q=-7q+10 | | 52-31=x | | -37+7x=40 | | s^3+3s^2+3s+1=0 | | s^3+4s^2+4s+1=0 | | 6x+12=-84+10x | | 12x-42=114 | | 13-6x=5-8x | | 7p-(3+4)=-2(2p-1)+10 | | 5(x-4)+3-9x=6-(2x+5)+8x | | 56+8x=128 | | 5x-2(x+1)=9 | | -16t^2+16t^2+896= | | 53-10x=17+8x | | 4x-44=0 | | -17r=-170 | | 4x+83=-7 | | 11x+1=12-4 | | z-20=15 |